Degradation of Methylene Blue Using Cadmium Sulfide Photoanode in Photofuel Cell System with Variation of Electrolytes - Gunawan Gunawan; Abdul Haris; Didik Setiyo Widodo; Linda Suyati; Wilman Septina (Universitas Gadjah Mada, 2021)
Methylene blue degradation carried out using cadmium sulfide (CdS) photoanode in photofuel cell (PFC) had been done. CdS synthesized by chemical bath deposition (CBD) on the FTO substrate was used as anode and platinum as a cathode in photoelectrochemical studies. Characterization of CdS thin film was done using EDX, XRD, SEM, Raman, UV-Vis absorption spectrophotometer as well as photocurrent test of the CdS thin film under illumination using potentiostat with the three-electrode system. The EDX result indicated the presence of CdS with an elemental composition of Cd rich. XRD showed the appearance of CdS crystals in cubic and hexagonal formations. SEM image of CdS gave results in the form of crystals of less than 1 mm. Raman spectrum showed the appearance of CdS peaks. The bandgap of CdS was estimated to be 2.38 eV, and the photocurrent test confirmed that the film had a property of n-type semiconductor. Application of CdS thin film as a photoanode in the PFC system using 100 mg/L methylene blue solution showed degradation up to 48% for 2.5 h using a 4 cm2 photoanode, and the maximum potential of 0.8 V was obtained with a photoanode area of 1 cm2.